The inherent paradox of clinical trials in psychiatry - Helmchen, H. (Journal of medical ethics, 1975)
The authors sum up the central issue of ethics in the conduct of controlled clinical trials in these two paradoxes: 'first, it is unethical to use treatment the efficacy of which has not been examined scientifically; second, it is also unethical to examine the efficacy of treatment scientifically.' In this paper they set out to demonstrate how these antithetical statements apply in controlled trials conducted in psychiatric patients. In such trials the problem of obtaining informed consent may be acute, but in these patients giving 'informed' consent might contribute to a further exacerbation of the illness. Nevertheless the problem cannot be evaded, and scientific judgments must be applied to treatment for it to be sound and improved for the further benefit of patients. These problems in the case of psychiatric controlled trials are a part of the methodology, and in Germany a new drug law has been drafted to attempt to clarify the issue. The authors briefly discuss its application, and its consequences if such a law were enacted. British psychiatrists have exactly the same problems to face but so far no attempts have been made to establish a legal framework.